Homotopic Approximate Solutions for the Perturbed CKdV Equation with Variable Coefficients - Dianchen Lu; Tingting Chen; Baojian Hong (The Scientific World Journal)
This work concerns how to find the double periodic form of approximate solutions of the perturbed combined KdV (CKdV) equation with variable coefficients by using the homotopic mapping method. The obtained solutions may degenerate into the approximate solutions of hyperbolic function form and the approximate solutions of trigonometric function form in the limit cases. Moreover, the first order approximate solutions and the second order approximate solutions of the variable coefficients CKdV equation in perturbation εun are also induced.